Comparisons of CVID and IgGSD: Referring Physicians, Autoimmune Conditions, Pneumovax Reactivity, Immunoglobulin Levels, Blood Lymphocyte Subsets, and HLA-A and -B Typing in 432 Adult Index Patients - James C. Barton; Luigi F. Bertoli; J. Clayborn Barton (Journal of Immunology Research)
Common variable immunodeficiency (CVID) and immunoglobulin (Ig) G subclass deficiency (IgGSD) are heterogeneous disorders characterized by respiratory tract infections, selective Ig isotype deficiencies, and impaired antibody responses to polysaccharide antigens. Using univariable analyses, we compared observations in 34 CVID and 398 IgGSD adult index patients (81.9% women) referred to a hematology/oncology practice. Similarities included specialties of referring physicians, mean ages, proportions of women, reactivity to Pneumovax, median serum IgG3 and IgG4 levels, median blood CD56+/CD16+ lymphocyte levels, positivity for HLA-A and -B types, and frequencies of selected HLA-A, -B haplotypes. Dissimilarities included greater prevalence of autoimmune conditions, lower median IgG, IgA, and IgM, and lower median CD19+, CD3+/CD4+, and CD3+/CD8+ blood lymphocytes in CVID patients. Prevalence of Sjögren’s syndrome and hypothyroidism was significantly greater in CVID patients. Combined subnormal IgG1/IgG3 occurred in 59% and 29% of CVID and IgGSD patients, respectively. Isolated subnormal IgG3 occurred in 121 IgGSD patients (88% women). Logistic regression on CVID (versus IgGSD) revealed a significant positive association with autoimmune conditions and significant negative associations with IgG1, IgG3, and IgA and CD56+/CD16+ lymphocyte levels, but the odds ratio was increased for autoimmune conditions alone (6.9 (95% CI 1.3, 35.5)).